The immunosuppressive microenvironment and immunotherapy in human glioblastoma - Zhang, Xuehua; Zhao, Leilei; Zhang, He; Zhang, Yurui; Ju, Huanyu; Wang, Xiaoyu; Ren, Huan; Zhu, Xiao; Dong, Yucui (Frontiers in Immunology, 2022)
Glioblastoma multiforme (GBM) is the most malignant intracranial tumors in adults, characterized by extensive infiltrative growth, high vascularization, and resistance to multiple therapeutic approaches. Among the many factors affecting the therapeutic effect, the immunosuppressive GBM microenvironment that is created by cells and associated molecules via complex mechanisms plays a particularly important role, facilitating evasion of the tumor from the immune response. Accumulating evidence is also revealing a close association of the gut microbiota with the challenges in the treatment of GBM. The gut microbiota establishes a connection with the central nervous system through bidirectional signals of the gut–brain axis, thus affecting the occurrence and development of GBM. In this review, we discuss the key immunosuppressive components in the tumor microenvironment, along with the regulatory mechanism of gut microbiota involved in immunity and metabolism in the GBM microenvironment. Lastly, we concentrate on the immunotherapeutic strategies currently under investigation, which hold promise to overcome the hurdles of the immunosuppressive tumor microenvironment and improve the therapeutic outcome for patients with GBM.